A newly discovered Late Cretaceous metamorphic belt along the active continental margin of the Neo-Tethys ocean - Wang, D; Liu, F-L; Palin, R; Wang, J-M; Wo, M; Ji, L; Wang, F (Geological Society of America, 2021)
High-grade metamorphic rocks and crustal melts provide crucial evidence for growth and differentiation of the continental crust, and are widespread in collisional orogens. However, their importance in the evolution of continental arcs remains poorly understood. Metamorphism and related anatexis in the preserved continental margin of the Neo-Tethys ocean serves as a key natural laboratory to investigate this process. Along the Neo-Tethyan arc margin, the Gaoli-gong shear zone, Yunnan region of China, is an important locality for linking Lhasa in the north with Sibumasu and Burma in the south. Here, Late Cretaceous granulitefacies metamorphism and crustal anatexis have been identified for the first time in the Gaoligong area. Zircon and monazite U-Pb dating indicates that S-type granites formed at 87-73 Ma, granites and buried pelitic sediments were simultaneously metamorphosed at 75-70 Ma during Neo-Tethyan subduction, and all lithologies were overprinted by a younger 40-30 Ma magmatic and strike-slip event related to India-Asia collision. Phase equilibria modeling of high-grade anatectic gneiss in the MnO-Na2O-CaO-K2O-FeO-MgO-Al2O3-SiO2-H2O-TiO2 system indicates peak pressure-temperature (P-T) conditions of 780-800 °C and 6.5-7.5 kbar and defines a cooling and decompressional P-T path for the metapelites. This demonstrates that sediments within the Neo-Tethyan active conti- nental arc were buried to >20 km depth at 75-70 Ma. In combination with the metamorphic record of the Lhasa, Burma, and Sibu-masu blocks, an extensive Late Cretaceous metamorphic belt must have formed along the Neo-Tethyan subduction zone. This spatially correlates with coeval gabbro-diorite suites exposed in the Gangdese, Sibumasu and Burma terranes that were triggered by thinning of the lithospheric mantle. This prolonged Late Cretaceous mantle-derived magmatism and lithospheric thinning may have provided a regional-scale heat source for high-grade metamorphism and crustal anatexis along the active continental margin of the Neo-Tethys ocean.